How does IPM 3.0 look like (and why do we need it in Africa)? - Tamò, Manuele; Glitho, I.A.; Tepa-Yotto, G.; Muniappan, R. (Elsevier, 2022)
The concept of Integrated Pest Management (IPM) was introduced sixty years ago to curb the overuse of agricultural pesticides, whereby its simplest version (IPM 1.0) was aiming at reducing the frequency of applications. Gradually, agro-ecological principles, such as biological control and habitat management, were included in IPM 2.0. However, throughout this time, smallholder farmers did not improve their decision-making skills and continue to use hazardous pesticides as their first control option. We are therefore proposing a new paradigm — IPM 3.0 — anchored on 3 pillars: 1) real-time farmer access to decision-making, 2) pest-management options relying on science-driven and nature-based approaches, and 3) the integration of genomic approaches, biopesticides, and habitat-management practices. We are convinced that this new paradigm based on technological advances, involvement of youth, gender-responsiveness, and climate resilience will be a game changer. However, this can only become effective through redeployment of public funding and stronger policy support.